Reconstructing Early Hydrologic Change in the California Delta and its Watersheds. Issue 10 (16th October 2018) - MacVean, Lissa J.; Thompson, Sally; Hutton, Paul; Sivapalan, Murugesu
Abstract: Regulatory goals for the California Delta attempt to restore natural ecosystems through various water management efforts. Defining management criteria for restoration is challenging, given that the earliest data describing the hydrology of the region follow many decades of change associated with agricultural development, channel modification, and flood control. This study explores the hydrology of the 1850–1920 period by synthesizing new reconstructed precipitation, basin inflows, land use change, and levee construction time series, in a semidistributed hydrologic model. The model demonstrated that it is impossible to simultaneously reproduce estimated historical flood extents, frequencies, and durations given contemporary topography. Bounding cases were constructed to span potential water budget partitioning and suggest that the state of this region by the 1920s was hydrologically similar to that of the natural regime (i.e., flow experienced was depressed due to drought, but within the bounds of variability of the natural Delta system), partly due to the flow augmentation provided by flood control infrastructure and enhanced channel conveyance. The model suggests that levee construction, rather than land use change, had the greatest impact on Delta hydrology. This and other reconstructions, however, suggest that decreases in annual Delta outflows accelerated after 1920. Future efforts to reconstruct Delta hydrology should focus on improving information about the historical topography and channel geometry of the Central Valley river network, with a view to refining understanding of the natural and historical flood regime. Plain Language Summary: The California Delta is a nexus of conflict between environmental, agriculture, and urban water interests. Current management approaches mandate restoration of the Delta ecosystems, yet appropriate hydrologic restoration targets are unclear. The earliest reliable flow records date to the 1920s, by which time the Delta watersheds had experienced many decades of land cover, flood control, and other changes. The impact of these changes on the measured flows is unclear. We reconstructed rainfall, basin inflows, land use and flood levy histories, and modeled 1850–1920 Delta outflows. The effect of human‐induced changes on annual Delta outflow ranged from a 40% increase in flow from 1850‐1920 depending on the assumed characteristics of the natural flood regime. We could not model a historical flood regime that matched reported peak flooded areas, typical flood durations, and the contemporary watershed topography. Regardless, the results indicate that annual Delta outflows in the 1920s were not depressed relative to natural conditions and that flood levee construction had the most important human impact on flow in the 1850–1920 period. Future work is needed to characterize the historical flood regime in the Central Valley watersheds and reduce the uncertainty surrounding the change in Delta Outflows in the 1850–1920 period. Key Points: Effects of human intervention on the California Delta outflows are unknown, but important for defining flow restoration targets Reconstructed outflows indicate minimal declines to substantial increases in Delta outflow attributable to human action from 1850 to 1920 Historic flood regime is the key uncertainty; further understanding of topographic change and historical flood extent is needed